2.5x - 3 + 2x = 1.75x - 1.25x + 13
4.5x - 3 = 0.50x + 13
4.0x = 16
x = 4
Answer: 4
2. We'll assume those xs are in the numerator
(3/7)x - 1/4 + (3/7)x = (9/7)x - (3/7)x + 3/4 - 1
(6/7)x - 1/4 = (6/7)x - 1/4
0 = 0
That's always true.
Answer: Any x is a solution.
Answer:
8) The y coordinate of the solution: 4
9) Average of change from x = 2 to x = 4: 11
Step-by-step explanation:
8)
y = 2x + 2
y = x^2 + 3
So
x^2 + 3 = 2x + 2
x^2 - 2x + 3 - 2 = 0
x^2 - 2x + 1 = 0
(x - 1)^2 = 0
x - 1 = 0
x = 1
Plug in x = 1 into either those 2 equations to find y
y = 2(1) + 2 = 4
or
y = (1)^2 + 3 = 1 + 3 = 4
Answer:
The y coordinate of the solution is 4
9)
p(x) = x^2 + 5x - 2
p(2) = 2^2 + 5(2) - 2 = 4 + 10 - 2 = 12
p(4) = 4^2 + 5(4) - 2 = 16 + 20 - 2 = 34
Average of change from x = 2 to x = 4:
[p(4) - p(2)]/[(x(4) - x(2)] = (34 - 12)/(4-2) = 22 /2 = 11
Answer:
Average of change from x = 2 to x = 4 :11
We have the expression:

And want to evaluate in y=5, this means we have to replace y in the expression for 5 and calculate the value of the expression, so:

The expression is 30 when y=5.
Answer:
if u put that in latin then in spanish then back in english then someone might actually be able to answer that
Step-by-step explanation:
Geometric sequence is a sequence of numbers that have a common ratio between them.